Modeling-Based Response-Guided Glecaprevir-Pibrentasvir Therapy for Chronic Hepatitis C to Identify Patients for Ultrashort Treatment Duration. (4th May 2020) - Dasgupta, Swikriti; Imamura, Michio; Gorstein, Evan; Nakahara, Takashi; Tsuge, Masataka; Churkin, Alexander; Yardeni, David; Etzion, Ohad; Uprichard, Susan L; Barash, Danny; Cotler, Scott J; Dahari, Harel; et al.
Abstract: We recently showed in a proof-of-concept study that real-time modeling-based response-guided therapy can shorten hepatitis C virus treatment duration with sofosbuvir-velpatasvir, elbasvir-grazoprevir, and sofosbuvir-ledipasvir without compromising efficacy, confirming our retrospective modeling reports in >200 patients. However, retrospective modeling of pibrentasvir-glecaprevir (P/G) treatment has yet to be evaluated. In the current study, modeling hepatitis C virus kinetics in 44 cirrhotic and noncirrhotic patients predicts that P/G treatment might have been reduced to 4, 6, and 7 weeks in 16%, 34%, and 14% of patients, respectively. These results support the further evaluation of a modeling-based response-guided therapy approach using P/G. Abstract : Retrospective mathematical modeling of early hepatitis C virus kinetics in 44 cirrhotic and noncirrhotic patients predicts that pibrentasvir-glecaprevir treatment might have been reduced to 4, 6, and 7 weeks in 16%, 34%, and 14% of patients, respectively.